City and politics in the Sacred Valley of the Incas: Report of a field investigation - Guadalupe, César (1991)
In 1987 we arrived in Cusco with the intention of carrying out an investigation on the characteristics of the State in the region. The debate with the other members of the research team, as well as our previous concerns, led us to raise the possibility of developing a field investigation aimed at accounting for how, in a particular space, the subjects develop a set of practices aimed at obtaining benefits. of the state offices present there. We seek to account for the state presence as a reference for the action of the subjects and of this as a central element for the configuration of the political space.